A cooperative scheduling method based on the device load feedback for multiple tasks scheduling. (1st December 2017) - Xin, Yu; Wang, Ya-Di; Xie, Zhi-Qiang; Yang, Jing
Abstract: With the development of cloud computing, the traditional Star Scheduling System with solo scheduler can not meet the requirement of distributed system. Thus, we designed a scheduling method, which can be applied into multi-scheduler system, denoted by MTDR (Multi Task Dynamic-Rank scheduling method). For the issue of device confliction in multi-scheduler system, we design the following scheduling principle: the devices feedback their load state to schedulers to control the successive scheduling process. For the device load modeling, we utilize time window method to predict the device's load state, denoted by LSF (Load State Feedback model). When the schedulers deal with the task slices, the device load state is considered. We performed experiments on the arrival time test, device dependence test, task structure test, CCR(communication computation ratios) test, Devices Set test. By experimental comparison, the effectiveness and rationality of the proposed method is verified.